Dramatic reduction in size of the lowland Macquarie River in response to Late Quaternary climate-driven hydrologic change. Issue 2 (19th September 2018) - Hesse, Paul P.; Williams, Rory; Ralph, Timothy J.; Larkin, Zacchary T.; Fryirs, Kirstie A.; Westaway, Kira E.; Yonge, David
Abstract: Palaeochannels of lowland rivers provide a means of investigating the sensitivity of river response to climate-driven hydrologic change. About 80 palaeochannels of the lower Macquarie River of southeastern Australia record the evolution of this distributive fluvial system. Six Macquarie palaeochannels were dated by single-grain optically stimulated luminescence. The largest of the palaeochannels (Quombothoo, median age 54 ka) was on average 284 m wide, 12 times wider than the modern river (24 m) and with 21 times greater meander wavelength. Palaeo-discharge then declined, resulting in a younger, narrower, group of palaeochannels, Bibbijibbery (125 m wide, 34 ka), Billybingbone (92 m, 20 ka), Milmiland (112 m, 22 ka), and Mundadoo (86 m, 5.6 ka). Yet these channels were still much larger than the modern river and were continuous downstream to the confluence with the Barwon-Darling River. At 5.5 ka, a further decrease in river discharge led to the formation of the narrow modern river, the ecologically important Macquarie Marshes, and Marra Creek palaeochannel (31 m, 2.1 ka) and diminished sediment delivery to the Barwon-Darling River as palaeo-discharge fell further. The hydrologic changes suggest precipitation was a driving forcing on catchment discharge in addition to a temperature-driven runoff response.